Penerapan Terapi Hortikultura pada Pasien Skizofrenia dengan Halusinasi - Hayuning Tyas Rahmadhani; Sri Padma Sari; Diyan Yuli Wijayanti (Journal of Innovative and Creativity, 2025)
Skizofrenia adalah gangguan jiwa kronis yang ditandai oleh halusinasi, kecemasan, dan gangguan fungsi psikososial. Terapi hortikultura merupakan pendekatan nonfarmakologis berbasis aktivitas alam yang mampu merangsang fungsi kognitif dan emosional serta mendukung proses pemulihan klien skizofrenia. Namun, di Indonesia, bukti ilmiah mengenai efektivitas terapi hortikultura individu berbasis komunitas terhadap gejala psikotik dan proses pemulihan masih terbatas. Penelitian ini bertujuan untuk mengevaluasi efektivitas terapi hortikultura untuk menurunkan gejala halusinasi dan kecemasan serta meningkatkan proses pemulihan psikososial pada klien skizofrenia di masyarakat. Penelitian ini menggunakan desain quasi-eksperimen dengan pendekatan one group pretest-posttest pada tiga klien skizofrenia dengan halusinasi pendengaran. Intervensi terapi hortikultura diberikan selama enam sesi dalam kurun waktu 10 hari. Pengukuran menggunakan instrumen Auditory Hallucination Rating Scale (AHRS), Generalized Anxiety Disorder-7 (GAD-7), dan Recovery Assessment Scale (RAS) versi Bahasa Indonesia. Setelah dilakukan intervensi, ketiga klien menunjukkan penurunan skor AHRS (25 menjadi 20; 22 menjadi 10; 22 menjadi 12) dan GAD-7 (15 menjadi11; 14 menjadi 6; 15 menjadi 9), serta peningkatan skor RAS (49 menjadi 60; 59 menjadi 70; 59 menjadi 64). Respons verbal dan perilaku klien juga menunjukkan peningkatan fokus, kestabilan emosi, dan motivasi untuk pemulihan. Terapi hortikultura efektif mengurangi tanda dan gejala halusinasi dan kecemasan serta mendukung proses pemulihan psikososial pada klien skizofrenia. Keywords: Skizofrenia; halusinasi; terapi hortikultura; kecemasan; pemulihan ABSTRACT Schizophrenia is a chronic mental disorder characterized by hallucinations, anxiety, and impaired psychosocial functioning. Horticultural therapy is a non-pharmacological, nature-based activity approach that can stimulate cognitive and emotional functions and support the recovery process in patients with schizophrenia. However, in Indonesia, scientific evidence on the effectiveness of community-based individual horticultural therapy on psychotic symptoms and recovery remains limited. This study aims to evaluate the effectiveness of community-based individual horticultural therapy in reducing hallucination and anxiety symptoms and improving psychosocial recovery in patients with schizophrenia. This study employed a quasi-experimental design with a one-group pretest-posttest approach involving three schizophrenia patients with auditory hallucinations. The intervention consisted of six horticultural therapy sessions over two weeks. Measurements were conducted using the Indonesian version of the Auditory Hallucination Rating Scale (AHRS), Generalized Anxiety Disorder-7 (GAD-7), and the Recovery Assessment Scale (RAS). Following the intervention, all three patients showed decreased AHRS scores (from 25 to 20; 22 to 10; 22 to 12) and GAD-7 scores (from 15 to 11; 14 to 6; 15 to 9), as well as increased RAS scores (from 49 to 60; 59 to 70; 59 to 64). Verbal and behavioral responses indicated improved focus, emotional stability, and motivation for recovery. Horticultural therapy is effective in reducing hallucinations and anxiety and supports psychosocial recovery in patients with schizophrenia. This intervention is feasible to integrate into community mental health nursing practice as an affordable, applicable, and sustainable complementary approach. Keywords: Schizophrenia; hallucinations; horticultural therapy; anxiety; recovery